Spatial heterogeneity in summer phytoplankton communities shaped by anthropogenic and natural effects in typical coastal bay-river systems in South China - Shuling Yu; Ze Ren; Yanli Yang; Cheng Zhang; Kang Ma; Yiliang Xie; Baoshan Cui; Yan Xu (Ecological Indicators, 2023)
Phytoplankton community spatial scales vary in typical coastal bay-river systems under natural and anthropogenic effects. However, their relative importance in shaping phytoplankton spatial heterogeneity has been largely uncharacterized in the literature. In this study, we performed comprehensive analyses using field monitoring, meteorological, and remote sensing datasets from a coastal bay-river system in South China (the Guangdong-Hong Kong-Macao Greater Bay-Pearl River tributaries) to examine phytoplankton spatial heterogeneity and main effects. We showed that water quality in the four water bodies of the typical coastal bay-river system in South China were relatively poor. Phytoplankton community abundance, taxonomic grouping, dominant species, and species similarity varied significantly in response to environmental gradients. We showed that Cyanophyta, Bacillatiophyta, and Chlorophyta were dominant phyla, and we observed regional variations in taxonomic groups and dominant species. Phytoplankton abundance was significantly higher in Dongjiang River and water bodies in branched bays when compared with other regions due to nutrient input from extensive agricultural and urban development, where the dominant phylum was Cyanophyta. Cyclotella (Bacillariophyta) had relatively high abundance and was widely distributed throughout the coastal bay-river system, except in the Dongjiang River. Melosira (Bacillariophyta) had relatively high abundance in Dongjiang and Xijiang Rivers, Merismopedia (Cyanophyta) dominated in the Dongjiang River and highly urbanized branched bay areas, while Microcystis (Cyanophyta) only dominated in Beijiang and Xijiang Rivers. Dominant species distributions showed apparent spatial heterogeneity in phytoplankton community composition. Species similarities between different water bodies were generally low, but phytoplankton species similarities between the Dongjiang River and water bodies in the branched bay area were relatively high, which indicated that water exchange associated with freshwater and nutrient inputs may have profoundly influenced species dispersal and dominant phytoplankton species. Redundancy analyses (RDA) demonstrated that pH, elevation, photosynthetically active radiation (PAR), dissolved active phosphorus (SRP), total dissolved phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO3−-N) values - associated with nutrient and climate indicators were the main factors explaining structured phytoplankton spatial distributions. Variance partitioning analyses (VPA) showed that phytoplankton community variations were explained by anthropogenic factors (eutrophication) in summer. Our study improves our understanding of the natural and anthropogenic effects on phytoplankton spatial heterogeneity and provides basic study data for long-term phytoplankton evolution from river to bay areas.